2011
DOI: 10.1038/oby.2010.137
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Relative Contributions of Intra‐Abdominal and Liver Fat to Components of the Metabolic Syndrome

Abstract: Abdominally obese individuals with the metabolic syndrome often have excess fat deposition both intra‐abdominally (IA) and in the liver, but the relative contribution of these two deposits to variation in components of the metabolic syndrome remains unclear. We determined the mutually independent quantitative contributions of IA and liver fat to components of the syndrome, fasting serum (fS) insulin, and liver enzymes and measures of hepatic insulin sensitivity in 356 subjects (mean age 42 years, mean BMI 29.7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
35
2

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 60 publications
(46 citation statements)
references
References 32 publications
9
35
2
Order By: Relevance
“…This finding was also observed by other authors 32,35 . Kotronen et al 32 found a positive and significant correlation between visceral fat and levels of TG, SBP and DBP (r = 0.36, 0.28 and 0.24, respectively) and a negative one with HDL (r = -0.38). Hayes et al 35 found, …”
Section: -Confidence Interval; Bmi -Body Mass Index; Vvf -Volume Osupporting
confidence: 81%
See 1 more Smart Citation
“…This finding was also observed by other authors 32,35 . Kotronen et al 32 found a positive and significant correlation between visceral fat and levels of TG, SBP and DBP (r = 0.36, 0.28 and 0.24, respectively) and a negative one with HDL (r = -0.38). Hayes et al 35 found, …”
Section: -Confidence Interval; Bmi -Body Mass Index; Vvf -Volume Osupporting
confidence: 81%
“…However, this finding was not observed in other studies 4,10,31,32 . Romero-Corral et al 6 draw attention to the fact that the visceral fat is associated with endothelial dysfunction, even in the absence of blood pressure alterations.…”
Section: -Confidence Interval; Bmi -Body Mass Index; Vvf -Volume Ocontrasting
confidence: 55%
“…Abdominal fat has been shown to be an independent risk factor for metabolic syndrome and cardiovascular disease [41], and contributes to health disease risk comparable to smoking [42]. Previous research has shown that a relatively modest decrease in waist circumference (WC) of ≥3 cm yielded significant improvement in cardiometabolic risk factors [43].…”
Section: Discussionmentioning
confidence: 99%
“…Although obesity is a major health concern, abdominal obesity is of greater clinical relevance. Accumulation of liver fat, including nonalcoholic fatty liver disease (NAFLD), is present in ;25% of adults in Western countries and has been proposed as a causative factor in the development of cardiometabolic disorders and type 2 diabetes (4)(5)(6)(7)(8). In obesity, the prevalence of NAFLD is extremely high and may reach 75% (9).…”
Section: Overfeeding Polyunsaturated and Saturated Fat Causes Distincmentioning
confidence: 99%